استجابة بعض صفات الحاصل النوعية في نبات الذرة الحلوة لمواعيد الزراعة والرش بالمحفزات الحيوية: محمد هادي عبيد و صادق قاسم صادق - هادي, محمد عبيد; صادق, محمد قاسم (Journal of Kerbala for Agricultural Sciences, 2016)
المستخلص نفذت التجربة في حقول الخضر التابعة لقسم البستنة وهندسة الحدائق – كلية الزراعة ( ابو غريب) – جامعة بغداد ، للموسم الخريفي 2012 والموسم الربيعي2013 ، بهدف دراسة تأثير مواعيد الزراعة و الرش بالمحفزات الحيوية والتداخل بينهما في بعض الصفات النوعية لنبات الذرة الحلوة (Zea mays L.var saccharata ) ، تضمنت تجربة الموسم الخريفي موعدين 1 اب و 15 اب و الموسم الربيعي على اربع مواعيد 15 شباط، و1 اذار، و 15 اذار، و 1 نيسان ، اشتمل كل موعد على المعاملة بثلاثة انواع من المحفزات الحيوية الاول Disper Root و Disper Chlorophyll وDisper Vita بتركيز 1غم/ لتر-1 ، ويمكن تلخيص نتائج التجربة كالاتي : اثرت مواعيد الزراعة معنويا في معظم الصفات النوعية ، حققت النباتات المزروعة في موعد 15 اب اعلى المعدلات في النسبة المئوية للزيت 2.36% ، والبروتين 6.15% . اما في الموسم الربيعي ، فقد حقق موعد 15 اذار اعلى المعدلات في النسبة المئوية للسكريات الكلية 11.38% والمواد الصلبة الذائبة الكلية 8.41%. و تميزت معاملة المحفز الحيوي Root2+Chloro في الموسمين الخريفي والربيعي بأفضل المعدلات لصفة النسبة المئوية للبروتين في الحبوب 6.41 و 4.58 % . وحقق التداخل ما بين مواعيد الزراعة والمحفزات الحيوية تأثير معنوي في بعض صفات النوعية ، وللموسمين الخريفي والربيعي على التوالي ، اذ اعطت المعاملة Chloro+Vital في الموعد15 اب التي اعطت اعلى المعدلات في النسبة المئوية للسكريات الكلية (11.62%) والنسبة المئوية للزيت 2.64%. اما في الموسم الربيعي المعاملة Root2+Chloro في موعد 15 اذار اعلى المعدلات في النسبة المئوية للسكريات الكلية 11.89%. . البحث مستل من اطروحة دكتوراه للباحث الاول* response of some quality yield traits of sweet corn (Zea mays L .var saccharata) for planting dates and spraying with biostemulators. Abstract Carried out the experiment in the vegetable fields of the Department of Horticulture and landscaping - Faculty of Agriculture - University of Baghdad, for the autumn season (2012) and the spring season 2013 in order to study response of some quality yield traits of sweet corn (Zea mays L .var saccharata) for planting dates and spraying with biostemulators. Experience autumn season included two dates August 1 and August 15 and the spring season on four dates 15 February, 1March, 15March, 1April , All included on the transaction date three types of biostemulators Disper Root, Disper Chlorophyll and Disper Vital concentration of 1 g. L-1, can be summarized results of the experiment as follows: planting dates affected in most of the significantly quality qualities, achieved cultivated plants in the date August 15, the highest in the percentage of oil 2.36%, protein 6.15%. In the spring season, it has achieved a date March 15, the highest in the percentage of total sugars 11.38% and TSS total 8.41%. And characterized the treatment of biostemulator Root 2 + Chloro in autumn and spring season the best rates for recipe percentage of protein in the grain 6.41 and 4.58%. And achieved the interference between planting dates and biostemulators significant effect in some recipes quality, and for two seasons, autumn and spring respectively, as given treatment Chloro + Vital on the date August 15, which gave the highest rates in the percentage of total sugars 11.62% and the percentage oil 2.64%. In the spring season treatment Root2 + Chloro later March 15, the highest in the percentage of total sugars 11.89%. Key words: sweet corn, Zea mays L .var saccharata , planting dates, biostemulators